Environmental Recovery in Ukraine: Assessing Damages and Forming Solutions - Romanovych, Anna (2022)
On February 24th of 2022, Russian Federation launched an unjustified full-scale invasion of Ukraine. Ukraine’s territory is approximately 603,550 km² and by the end of 2022, Moscow controlled 16.55% of Ukrainian territory (approximately 128,57 km), despite Ukraine’s liberation of about 700 km2 of its territory in December 2022 and 3,800 km2 in November 2022. In addition to the occupation of the territories, Russian invasion has significantly damaged Ukrainian infrastructure, livelihoods and critical energy and water provision sources. The estimated overall damage is 63 billion dollars worth, not to mention 4,431 residential buildings, 92 factories/enterprises, 378 educational institutions, 138 healthcare facilities, 8 civilian airports and 10 military airfields, and 8 thermal power plants/hydroelectric power plants destroyed so far. Combined with the official records of the crimes against humanity committed, it makes Ukrainian officials talk about the genocidal nature of this war. But it’s not only human deaths that the Russian war causes, Ukrainian officials also claim that Russia is causing an “ecocide” to the Ukrainian environment. Since the beginning of the war, Ministry of Environmental Protection and Natural Resources of Ukraine has recorded nearly 2,300 cases of environmental damage caused by the hostilities. Ministries estimate that about 2.9 million hectares of the country's protected areas, home to thousands of species of plants and animals, are under threat of irreversible destruction. Up until 1 March 2022, the aggressor has conducted hostilities on the territory of 900 nature reserve sites with an area of 12 406.6 km², which is about a third of the area of the nature reserve fund of Ukraine. Multiple ecosystems and species valuable to humanity are in danger, being under Russian occupation until this day. The speed and scale of this environmental destruction demonstrate a lack of protection for natural resources under international legislation. In addition to it all, the Russian war in Ukraine is directly contributing to climate change worldwide, and its consequences will be heavily lingering for generations to come, unless stopped before it’s too late. This thesis is a response to the Ukrainian civil organisations’ call for addressing an environmental aspect of this war by academics. It aims to assess the damage done to the environment of Ukraine, overview environmental recovery solutions available and intends to form a draft project proposals that may be of interest for environmental restoration efforts for Ukraine in the future.